ANALISIS DIFUSI DAN POLA SPASIAL SEBARAN PANDEMI COVID-19 DI KABUPATEN ASAHAN - Jaya, Muhammad Awaluddin; Marbun, Yessi Karolina; Lubis, Darwin Parlaungan; Rahmadi, M. Taufik (Jurnal Spasial, 2021)
Coronavirus is a virus that infects the human body where this virus causes humans exposed to this virus to experience mild to severe illness. This coronavirus has spread almost all over the world, one of which is Indonesia, precisely in Asahan Regency. The purpose of this study was to determine the diffusion and spatial pattern of the Covid-19 pandemic that occurred in the Asahan Regency. The data analysis technique in this study uses qualitative research with a descriptive analysis method in which the data and all information are described using a geographic information system. The results obtained are that based on the diffusion and spatial distribution pattern of COVID-19 in Asahan Regency, it is classified based on Confirmed Cases, Active Cases, Recovered, Died, and Suspected. Where, when viewed from confirmed cases, active cases, recovered, died, and suspected the highest spatial distribution pattern in Asahan Regency is in the Kisaran Timur District.